The Didactic Power of Socialization and Tradition: Christian Education and Javanese Bridal Customs - Stephanus Prihadi; Juanda Manullang (LP. Ma'arif Janggan Magetan, 2024)
This research explores the Javanese Bridal Meeting Tradition at GITJ in one of the districts in Central Java Province through the lens of sociology of Christian religious education. The tradition encompasses ten key stages, from the Sanggan handover to Sungkeman, each laden with symbolic meanings. The study employs descriptive qualitative methods, gathering data via observation, interviews, and literature review. Findings reveal the tradition's function as a socialization mechanism, reinforcing social norms and fostering community cohesion. From a Christian education perspective, it serves to impart Christian values within marriage and family life. Gereja Injil Tanah Jawa (GITJ) in one of the districts in Central Java Province community exhibits a positive stance towards preserving this tradition, viewing it as an integral part of their cultural identity, consistent with Christian principles. In conclusion, the Javanese Bridal Meeting Tradition at Banyutowo not only preserves cultural heritage but also serves as a means of social and religious education relevant to contemporary society, bridging traditional values and Christian teachings.